The role of dendritic cells in immunity against primary Herpes Simplex Virus infections - Bedoui, Sammy; Greyer, Marie (Frontiers in Microbiology, 2014)
Herpes simplex virus (HSV) is a DNA virus with tropism for infecting skin and mucosal epithelia during the lytic stages of its complex life cycle. The immune system has evolved a multitude of strategies to respond to primary HSV infections. These include rapid innate immune responses largely driven by pattern recognition systems and protective anti-viral immunity. Dendritic cells (DC) represent a versatile and heterogenic group of antigen presenting cells that are important for pathogen recognition at sites of infection and for priming of protective HSV-specific T cells. Here we will review the current knowledge on the role of DCs in the host immune response to primary HSV infection. We will discuss how DCs integrate viral cues into effective innate immune responses, will dissect how HSV infection of DCs interferes with their capacity to migrate from sites of infection to the draining lymph nodes and will outline how migratory DCs can make antigens available to lymph node resident DCs. The role of distinct DC subsets and their relevant contribution to antigen presentation on MHC class I and MHC class II molecules will be detailed in the context of T cell priming in the lymph node and the elicitation of effector function in infected tissues. An improved understanding of the fundamental mechanisms of how DCs recognize HSV, process and present its antigens to naïve and effector T cells will not only assist in the improvement of vaccine-based preventions of this important viral disease, but also serves as a paradigm to resolve basic immunological principles.